Ordböcker i svenska ur finskspråkiga studenters synvinkel - Wikström, Kaj (Nordiske Studier i Leksikografi, 1997)
The article is concerned generally with the difficulties faced by Finnish learners of Swedish, particularly at university level, in extracting lexical information from dictionaries. To what extent are dictionaries compiled to satisfy the needs of those studying Swedish? The background to this question is the results of a survey carried out among Finnish high school pupils. More specifically, the article examines, as a set of examples, the ways in which various dictionaries indicate syllable length. It tums out that a lack of consistency is surprisingly common. Students who are learning Swedish without a teacher need, but frequently fail to get, a clear indication of vowel or consonant quantity.